Prodasineura sangkhla sp. nov., a new damselfly from western Thailand (Odonata: Platycnemididae) - Keetapithchayakul, Tosaphol Saetung; Makbun, Noppadon; Ignatius, Kaewpawika Jitthamma; Phan, Quoc Toan (Zootaxa, 2024)
Prodasineura sangkhla sp. nov. is described from the Takhian Thong waterfall near the Thai-Myanmar border, Kanchanaburi Province, Thailand. It differs from all other species of Prodasineura Cowley, 1934 by the combination of the characters including white pruinescence on prothorax, synthorax and some parts of legs, blue markings on S10 and anal appendages, shape of anal appendages in males, and shape of occipital band and posterior process of posterior lobe in females.